Pendampingan Digitalisasi Pencatatan Data Siswa pada Buku Induk untuk Meningkatkan Efektivitas Administrasi di SMK Nurul Jadid - Anis Yusrotun Nadhiroh; Ana Ni’matul Mar’ah (Cahaya Pengabdian, 2026)
This community service activity aims to provide guidance on digitizing student data records in the master student register to enhance administrative effectiveness at SMK Nurul Jadid. The master student register is a crucial document containing essential student information and serves as the foundation for school administrative services. However, manual record-keeping often leads to issues such as data entry errors, difficulties in information retrieval, data duplication, and inefficient data recapitulation processes. The activity employed a participatory guidance approach comprising several stages: observation and needs analysis, program planning, preparation of the digital register format, implementation of guidance, monitoring and evaluation, and follow-up. The guidance process involved presentations, discussions, and hands-on practice using the digital format for data entry, editing, retrieval, categorization, and storage. The results indicate that the digitization guidance improved the administrative staff's ability to manage student data in a more organized, accurate, accessible, and efficient manner. Furthermore, the digital format facilitated faster data retrieval and easier information updates, while also supporting orderly school administration. It is hoped that the digitization of student records in the master register will be sustained following this activity, thereby supporting the improvement of administrative service quality at SMK Nurul Jadid.